Preparation method and application of efficient treatment agent for heavy metal wastewater
By activating ore industrial solid waste and pore-making agents under microwave heating conditions, and combining hydrothermal reaction technology, a treatment agent with excellent heavy metal ion removal ability is prepared, solving the problems of low treatment efficiency and large resource waste in the prior art.
Patent Information
- Application Number
- CN202510302048.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-14
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-03-14
AI Technical Summary
The prior art has problems of low treatment efficiency and waste of resources and energy when treating heavy metal wastewater, especially the low preparation reaction efficiency of zeolite, resulting in long synthesis time, low yield and purity.
Ore industrial solid waste, water and pore-making agent are mixed, granulated, dried and calcined to form porous adsorption matrix particles. Then, the activation reaction is carried out under microwave heating conditions, and the liquid assisted activation system of coke powder, alkaline substances and water is combined to further activate the adsorbed matrix particles. Then a hydrothermal reaction was carried out, and a treatment agent with excellent heavy metal ion removal ability was synthesized using tetraethylammonium hydroxide, sodium silicate saturated liquid and sodium aluminate saturated liquid.
It significantly reduces the synthesis time of the treatment agent, improves the removal capacity of heavy metal ions in wastewater, reduces waste of resources and energy, and reduces treatment costs.
Smart Images

Figure CN119793403A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wastewater treatment, and in particular to a preparation method and application of a high-efficiency heavy metal wastewater treatment agent. Background Art
[0002] The information disclosed in this background technology section is only intended to increase the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information has become the prior art known to ordinary technicians in the field.
[0003] With the rise of mining, chemical industry and other industries, the large-scale use of fertilizers and pesticides, and the unreasonable stacking of waste such as electronic waste, a large amount of heavy metal ions have poured into rivers, lakes and other water bodies. How to effectively treat them has become one of the current problems to be solved. The main treatment methods currently include: chemical precipitation, membrane separation technology, electrolysis, adsorption, etc. Among them, chemical precipitation refers to the addition of sulfide, lime, polyferric sulfate and other agents to wastewater to form precipitation with heavy metal ions in water, and then remove heavy metals by sedimentation or filtration. However, it is easy to cause secondary pollution of water bodies during the process. In addition, in recent years, my country's discharge standards for industrial wastewater containing heavy metals have become increasingly stringent, and simple chemical precipitation methods have been difficult to meet discharge requirements. Membrane separation technology is a method of separating and concentrating heavy metal ions in the liquid phase using a semipermeable membrane under certain pressure conditions. It has the characteristics of simple process, high selectivity, and the ability to recover heavy metals. However, a large number of supporting equipment are required, resulting in a high treatment cost for this method and it is not easy to apply on a large scale. The electrolysis method is to reduce and precipitate heavy metal ions in wastewater on the cathode plate to achieve the purpose of removing heavy metals. This method has problems such as plate corrosion, high power consumption and unstable treatment effect.
[0004] The adsorption method mainly relies on specific adsorption materials to remove heavy metal ions from water. This method has been widely used in the field of wastewater treatment due to its many advantages such as simple operation and low energy consumption. There are many gaps on the surface and inside of analcime, and the specific surface area is large. It can remove heavy metal ions in the solution through exchange, and its skeleton is negatively charged, which has a strong electrostatic attraction to cations in the water. Therefore, analcime is considered to be an efficient adsorption material that can be used to treat heavy metal wastewater. Analcime can be prepared from industrial solid waste and natural minerals rich in silicon and aluminum through hydrothermal reaction, but this method has low reaction efficiency, resulting in a reaction time of more than 48 hours, and there are problems with low yield and low purity of the generated crystal product, resulting in a large amount of resource and energy waste. Summary of the invention
[0005] The present invention provides a preparation method and application of a high-efficiency heavy metal wastewater treatment agent, which not only effectively reduces the synthesis time of the treatment agent, but also the obtained treatment agent has excellent removal ability for heavy metal ions in wastewater. Specifically, the technical solution of the present invention is as follows.
[0006] First, the present invention provides a method for preparing a high-efficiency heavy metal wastewater treatment agent, comprising the following steps: (1) Mix the ore industrial solid waste powder, water and pore-forming agent to form a wet mixture, dry the obtained particles after granulation, and then calcine them to obtain adsorption matrix particles for use.
[0007] (2) The adsorption matrix particles, coke powder, alkaline substance and water are mixed, and then activated under microwave heating conditions, and then naturally cooled to room temperature. Then, the reaction system is separated into solid and liquid, and the obtained solid and liquid phases are used separately.
[0008] (3) The solid material is subjected to a secondary microwave activation treatment to obtain a precursor for later use.
[0009] (4) The liquid phase is mixed with a mixture of precursors, tetraethylammonium hydroxide (TEAH), a saturated sodium silicate solution and / or a saturated sodium aluminate solution, and then subjected to a hydrothermal reaction. After completion, the mixture is cooled to room temperature, and then a solid product is separated, washed to neutrality, dried, and ground to obtain a powdery treatment agent.
[0010] Furthermore, in step (1), the ore-based industrial solid waste includes at least one of coal gangue, fly ash, and kaolin. Optionally, the fineness of the ore-based industrial solid waste powder is 200-500 mesh.
[0011] Furthermore, in step (1), the mass ratio of the mineral industrial solid waste to the pore-forming agent is 1: 0.0475~0.1. Optionally, the pore-forming agent includes at least one of β-polypropylene powder, polyethylene powder, rubber powder, etc. Optionally, the fineness of the pore-forming agent is 40~60 mesh. In this process, the pore-forming agent will be uniformly attached to the inside and surface of the particles. In the subsequent calcination process, open pores are formed inside and on the surface of the particles, and these pores will gradually close as the zeolite gradually crystallizes and grows.
[0012] Furthermore, in step (1), the moisture content of the wet mix is 30-35 wt.%.
[0013] Furthermore, in step (1), the particle size of the particles is 10-15 mm, and any other suitable particle size may be selected as required.
[0014] Furthermore, in step (1), the calcination treatment is carried out at a temperature of 600-900° C. and for a time of 1.5-2 h.
[0015] Furthermore, in step (2), the mass ratio of the adsorption matrix particles, coke powder, alkaline substance, and water is 1: 0.2-0.5: 0.13-0.22: 0.38-0.6. Optionally, the fineness of the coke powder is 400-700 mesh. The coke powder can strongly absorb microwaves and promote the adsorption matrix particles to release more silicon and aluminum elements.
[0016] Furthermore, in step (2), the alkaline substance includes at least one of sodium hydroxide, potassium hydroxide, and ammonia water.
[0017] Furthermore, in step (2), the power of the microwave is 300-500 W, the temperature of the activation reaction is 100-200° C., and the reaction time is 50-90 min.
[0018] Furthermore, in step (3), the power of the microwave heating treatment is 500-650 W, the heating temperature is 200-250° C., and the treatment time is 50-90 min.
[0019] Furthermore, in step (4), the mass ratio of the mixture to tetraethylammonium hydroxide is 1:0.26-0.40.
[0020] Furthermore, in step (4), the saturated sodium silicate solution and the saturated sodium aluminate solution are added according to the silicon to aluminum molar ratio of 1.4 to 3.3:1 in the reaction system.
[0021] Furthermore, in step (4), the temperature of the hydrothermal reaction is 100-120° C., and the time is 8-12 hours.
[0022] Furthermore, in step (4), the fineness of the treatment agent is 100-300 mesh.
[0023] Secondly, the present invention provides the application of the high-efficiency heavy metal wastewater treatment agent obtained by the above-mentioned preparation method in the fields of environment, chemical industry, water conservancy, wastewater treatment, etc. When used, the treatment agent is added to the heavy metal contaminated water body to be treated and mixed evenly, and the addition ratio can be selected according to actual needs.
[0024] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects: The preparation process proposed in the present invention not only effectively reduces the synthesis time of the treatment agent, but also the obtained treatment agent has excellent removal ability for heavy metal ions in wastewater. This is because: the present invention first prepares the porous adsorption matrix particles, which is not only conducive to the subsequent penetration of alkali solution during the activation reaction, improving the activation efficiency of the adsorption matrix particles, but also provides a fixed place for the subsequent formation of analcime, and obtains the target product more efficiently and quickly, reducing the synthesis time and cost. Furthermore, the present invention uses a liquid-assisted activation system formed by coke powder, alkaline substances and water to perform an activation reaction on the adsorption matrix particles. The coke powder can induce vibration and friction at the molecular level after assisting in the absorption of microwaves, and transfer energy to the interior of the particles more evenly and effectively, reducing energy consumption while improving the efficiency of microwave activation, and can significantly increase the activation degree of the adsorption matrix particles, and more activated particles are conducive to releasing silicon and aluminum elements into the liquid-assisted activation system to form silicate and aluminate monomers. At the same time, in this process, the pores reserved by the pore-forming agent in the adsorption matrix particles provide a better penetration channel for the alkaline solution formed by the alkaline substance, increase the contact between the particles and the alkaline solution, and promote the release of the silicon and aluminum elements. In addition, after part of the coke powder becomes part of the final treatment agent, its good adsorption performance also helps to promote the ability of the adsorbent to absorb heavy metal ions. Furthermore, the present invention performs microwave secondary activation on the adsorption matrix particles / the solid matter after the microwave activation treatment, so that the insoluble substances therein undergo the activation process again, thereby releasing silicate and aluminate monomers to the greatest extent, so as to facilitate the extraction by the alkaline liquid phase system in step (4) to provide active substances for the synthetic zeolite. Finally, the present invention uses TEAH, sodium silicate saturated solution and / or sodium aluminate saturated solution, and uses the liquid phase obtained in step (2) and the precursor obtained in step (3) as the reaction system to synthesize a treatment agent with excellent heavy metal ion removal ability. This is because: the pores synthesized in the precursor provide a place for zeolite crystallization during this process, so that a large amount of alkaline solution and active ions required for synthesizing analcime flow through the precursor, and the tetraethylammonium hydroxide uses its own molecular structure advantages to enter the framework of silicate and aluminate to construct a unique pore structure, and this pore structure is retained during the crystallization process to form a unique crystal form of analcime, improving its ability to adsorb heavy metal ions. At the same time, the tetraethylammonium hydroxide also helps to adjust the pH value of the reaction system and accelerate the synthesis of analcime. In addition, the sodium silicate saturated solution and / or sodium aluminate saturated solution effectively ensure the integrity and purity of the formed analcime structure and improve the adsorption capacity for heavy metal ions. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0026] Figure 1 The following are sample images of the treatment agents prepared in Examples 1 to 8.
[0027] Figure 2 The following are the XRD test results of the treating agents prepared in Examples 1 to 8.
[0028] Figure 3 The relative crystallinity test results of the treating agents prepared in the following Examples 1 to 8 are shown.
[0029] Figure 4 The following are the test results of the adsorption rate of heavy metal ions by the treatment agents prepared in Examples 1 to 8. DETAILED DESCRIPTION
[0030] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or according to the conditions recommended by the manufacturer.
[0031] Unless otherwise defined, all professional and scientific terms used in the present invention have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. If there are no special instructions, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar to or equivalent to the described content can be applied to the method of the present invention. Now, the technical solution of the present invention is further described in conjunction with the accompanying drawings and specific embodiments of the specification.
[0032] Example 1 A method for preparing a high-efficiency heavy metal wastewater treatment agent comprises the following steps: (1) 200 mesh coal gangue powder and 50 mesh β-polypropylene powder were mixed in a mass ratio of 1:0.05 and stirred evenly with water to form a wet mixture with a moisture content of 32 wt.%. After granulation, the obtained particles (average diameter 10.5±0.5 mm) were placed in an oven at 105°C for drying for 24 h. The particles were then placed in a muffle furnace and heated to 600°C at a heating rate of 300°C / h and kept warm for 2 h. After completion, they were naturally cooled to room temperature to obtain adsorption matrix particles for use.
[0033] (2) The adsorption matrix particles, 500-mesh coke powder, sodium hydroxide, and water are placed in a reaction tank and stirred in a mass ratio of 1:0.3:0.14:0.4. After the sodium hydroxide is fully dissolved, an activation reaction is carried out under microwave heating conditions. The power of the microwave heating is 300 W, the temperature of the activation reaction is 100°C, and the reaction time is 50 minutes. After completion, it is naturally cooled to room temperature. Then the obtained reaction system is placed in a centrifuge (speed 8000r) and centrifuged for 5 minutes. The obtained lower solid and upper liquid phases are set aside.
[0034] (3) The lower layer of solid matter is subjected to microwave heating treatment (temperature 200° C., power 650 W, insulation time 50 min), and a precursor is obtained after completion, which is set aside.
[0035] (4) The liquid phase of step (2) is first mixed with the precursor of step (3) to form a mixture, and then the mixture is mixed with tetraethylammonium hydroxide at a mass ratio of 1:0.3 and stirred evenly, and then saturated sodium silicate solution and saturated sodium aluminate solution are added to adjust the silicon-aluminum molar ratio in the reaction system to 1.5:1. The obtained reaction system is then heated to 100°C and kept warm for 12 hours for hydrothermal reaction, and then naturally cooled to room temperature after completion. The obtained reaction system and the precursor are placed in a centrifuge (speed 8000r) and centrifuged for 5 minutes. The lower layer of solid product is washed with clean water until neutral, and then placed in an oven at 105°C for 12 hours to dry, and then ground and passed through a 200-mesh sieve to obtain the treatment agent, such as Figure 1 shown.
[0036] Example 2 A method for preparing a high-efficiency heavy metal wastewater treatment agent comprises the following steps: (1) 500-mesh kaolin and 60-mesh polyethylene powder were mixed in a mass ratio of 1:0.0475 and stirred evenly with water to form a wet mixture with a moisture content of 30 wt.%. After granulation, the obtained particles (average diameter 12.5±0.5 mm) were placed in an oven at 105°C for drying for 24 h. The particles were then placed in a muffle furnace and heated to 800°C at a heating rate of 300°C / h and kept warm for 2 h. After completion, they were naturally cooled to room temperature to obtain adsorption matrix particles for use.
[0037] (2) The adsorption matrix particles, 700 mesh coke powder, sodium hydroxide, and water are placed in a reaction tank in a mass ratio of 1:0.2:0.13:0.38 and stirred. After the sodium hydroxide is fully dissolved, an activation reaction is carried out under microwave heating conditions. The power of the microwave heating is 400 W, the temperature of the activation reaction is 150°C, and the reaction time is 70 minutes. After completion, it is naturally cooled to room temperature. Then the obtained reaction system is placed in a centrifuge (speed 8000r) and centrifuged for 5 minutes, and the obtained lower solid and upper liquid phases are set aside.
[0038] (3) The lower layer of solid matter is subjected to microwave heating treatment (temperature 250° C., power 500 W, insulation time 75 min), and a precursor is obtained after completion, which is set aside.
[0039] (4) The liquid phase of step (2) is first mixed with the precursor of step (3) to form a mixture, and then the mixture is mixed with tetraethylammonium hydroxide at a mass ratio of 1:0.4 and stirred evenly, and then saturated sodium silicate solution and saturated sodium aluminate solution are added to adjust the silicon-aluminum molar ratio in the reaction system to 3.3:1. The obtained reaction system is then heated to 105°C and kept warm for 10 hours for hydrothermal reaction, and then naturally cooled to room temperature after completion. The obtained reaction system and the precursor are placed in a centrifuge (speed 8000r) and centrifuged for 5 minutes. The lower layer of solid product is washed with clean water until neutral, and then placed in an oven at 105°C for 10 hours to dry, and then ground and passed through a 300-mesh sieve to obtain the treatment agent, such as Figure 1 shown.
[0040] Example 3 A method for preparing a high-efficiency heavy metal wastewater treatment agent comprises the following steps: (1) 300-mesh fly ash and 40-mesh waste rubber powder were mixed in a mass ratio of 1:0.1 and stirred evenly with water to form a wet mixture with a moisture content of 35 wt.%. After granulation, the obtained particles (average diameter 14.5±0.5 mm) were placed in an oven at 105°C for drying for 24 h. The particles were then placed in a muffle furnace and heated to 900°C at a heating rate of 300°C / h and kept warm for 1.5 h. After completion, they were naturally cooled to room temperature to obtain adsorption matrix particles for use.
[0041] (2) The adsorption matrix particles, 400 mesh coke powder, potassium hydroxide, and water are placed in a reaction tank and stirred in a mass ratio of 1:0.5:0.22:0.6. After the potassium hydroxide is fully dissolved, an activation reaction is carried out under microwave heating conditions. The power of the microwave heating is 500 W, the temperature of the activation reaction is 200°C, and the reaction time is 90 minutes. After completion, it is naturally cooled to room temperature. Then the obtained reaction system is placed in a centrifuge (speed 8000r) and centrifuged for 5 minutes. The obtained lower solid and upper liquid phases are set aside.
[0042] (3) The lower layer of solid matter is subjected to microwave heating treatment (temperature 220° C., power 450 W, insulation time 90 min), and a precursor is obtained after completion, which is set aside.
[0043] (4) The liquid phase of step (2) is first mixed with the precursor of step (3) to form a mixture, and then the mixture is mixed with tetraethylammonium hydroxide at a mass ratio of 1:0.26 and stirred evenly, and then saturated sodium silicate solution and saturated sodium aluminate solution are added to adjust the silicon-aluminum molar ratio in the reaction system to 1.4:1. The obtained reaction system is then heated to 120°C and kept warm for 8 hours to carry out a hydrothermal reaction, and then naturally cooled to room temperature after completion. The obtained reaction system and the precursor are placed in a centrifuge (speed 8000r) and centrifuged for 5 minutes. The lower layer of solid product is washed with clean water until neutral, and then placed in an oven at 120°C to dry for 8 hours, and then ground and passed through a 100-mesh sieve to obtain the treatment agent, such as Figure 1 shown.
[0044] Example 4 A method for preparing a high-efficiency heavy metal wastewater treatment agent comprises the following steps: (1) 200 mesh coal gangue powder and 50 mesh β-polypropylene powder were mixed in a mass ratio of 1:0.05 and stirred evenly with water to form a wet mixture with a moisture content of 32 wt.%. After granulation, the obtained particles (average diameter 10.5±0.5 mm) were placed in an oven at 105°C for drying for 24 h. The particles were then placed in a muffle furnace and heated to 600°C at a heating rate of 300°C / h and kept warm for 2 h. After completion, they were naturally cooled to room temperature to obtain adsorption matrix particles for use.
[0045] (2) The adsorption matrix particles, 500-mesh coke powder, sodium hydroxide, and water are placed in a reaction tank and stirred in a mass ratio of 1:0.3:0.14:0.4. After the sodium hydroxide is fully dissolved, an activation reaction is carried out under microwave heating conditions. The power of the microwave heating is 300 W, the temperature of the activation reaction is 100°C, and the reaction time is 50 minutes. After completion, it is naturally cooled to room temperature. Then the obtained reaction system is placed in a centrifuge (speed 8000r) and centrifuged for 5 minutes. The obtained lower solid and upper liquid phases are set aside.
[0046] (3) The lower layer of solid matter is subjected to microwave heating treatment (temperature 200° C., power 650 W, insulation time 50 min), and a precursor is obtained after completion, which is set aside.
[0047] (4) The liquid phase of step (2) is first mixed with the precursor of step (3) to form a mixture, and then a saturated sodium silicate solution and a saturated sodium aluminate solution are added to adjust the silicon-aluminum molar ratio in the reaction system to 1.5:1. The obtained reaction system is then heated to 100°C and kept warm for 12 hours for hydrothermal reaction, and then naturally cooled to room temperature after completion. The obtained reaction system and the precursor are placed in a centrifuge (speed 8000r) and centrifuged for 5 minutes. The lower layer of solid product is washed with clean water until neutral, and then placed in an oven at 105°C for 12 hours to dry, and then ground and sieved through a 200-mesh sieve to obtain the treatment agent, such as Figure 1 shown.
[0048] Example 5 A method for preparing a high-efficiency heavy metal wastewater treatment agent comprises the following steps: (1) 300-mesh fly ash and 40-mesh waste rubber powder were mixed in a mass ratio of 1:0.1 and stirred evenly with water to form a wet mixture with a moisture content of 35 wt.%. After granulation, the obtained particles (average diameter 14.5±0.5 mm) were placed in an oven at 105°C for drying for 24 h. The particles were then placed in a muffle furnace and heated to 900°C at a heating rate of 300°C / h and kept warm for 1.5 h. After completion, they were naturally cooled to room temperature to obtain adsorption matrix particles for use.
[0049] (2) The adsorption matrix particles, 400-mesh coke powder, potassium hydroxide, and water are placed in a reaction tank in a mass ratio of 1:0.5:0.22:0.6 and stirred. After the potassium hydroxide is fully dissolved, an activation reaction is carried out under microwave heating conditions. The microwave heating power is 500 W, the activation reaction temperature is 200° C., and the reaction time is 90 min. After completion, the mixture is naturally cooled to room temperature, and the obtained solid-liquid reaction system is ready for use.
[0050] (3) The solid-liquid reaction system of step (2) is mixed with tetraethylammonium hydroxide at a mass ratio of 1:0.26 and stirred evenly, and then saturated sodium silicate solution and saturated sodium aluminate solution are added to adjust the silicon-aluminum molar ratio in the reaction system to 1.4:1. The obtained reaction system is then heated to 120°C and kept warm for 8 hours for hydrothermal reaction, and then naturally cooled to room temperature after completion. The obtained reaction system and the precursor are placed in a centrifuge (speed 8000r) and centrifuged for 5 minutes. The lower layer of solid product is washed with clean water until neutral, and then placed in an oven at 120°C for 8 hours to dry, and then ground and passed through a 100-mesh sieve to obtain the treatment agent, such as Figure 1 shown.
[0051] Example 6 A method for preparing a high-efficiency heavy metal wastewater treatment agent comprises the following steps: (1) 500-mesh kaolin and 60-mesh polyethylene powder were mixed in a mass ratio of 1:0.0475 and stirred evenly with water to form a wet mixture with a moisture content of 30 wt.%. After granulation, the obtained particles (average diameter 12.5±0.5 mm) were placed in an oven at 105°C for drying for 24 h. The particles were then placed in a muffle furnace and heated to 800°C at a heating rate of 300°C / h and kept warm for 2 h. After completion, they were naturally cooled to room temperature to obtain adsorption matrix particles for use.
[0052] (2) The adsorption matrix particles, 700 mesh coke powder, sodium hydroxide, and water are placed in a reaction tank in a mass ratio of 1:0.2:0.13:0.38 and stirred. After the sodium hydroxide is fully dissolved, an activation reaction is carried out under microwave heating conditions. The power of the microwave heating is 400W, the temperature of the activation reaction is 150°C, and the reaction time is 70 minutes. After completion, it is naturally cooled to room temperature. Then the obtained reaction system is placed in a centrifuge (speed 8000r) and centrifuged for 5 minutes to obtain a lower layer of solid matter and an upper layer of liquid phase, and then the upper layer of liquid phase is replaced with an equal volume of clean water for standby use.
[0053] (3) The lower layer of solid matter is subjected to microwave heating treatment (temperature 250° C., power 500 W, insulation time 75 min), and a precursor is obtained after completion, which is set aside.
[0054] (4) The clean water of step (2) and the precursor of step (3) are first mixed to form a mixture, and then the mixture is mixed with tetraethylammonium hydroxide at a mass ratio of 1:0.4 and stirred evenly, and then saturated sodium silicate solution and saturated sodium aluminate solution are added to adjust the silicon-aluminum molar ratio in the reaction system to 3.3:1. The obtained reaction system is then heated to 105°C and kept warm for 10 hours for hydrothermal reaction, and then naturally cooled to room temperature after completion. The obtained reaction system and the precursor are placed in a centrifuge (speed 8000r) and centrifuged for 5 minutes. The lower layer of solid product is washed with clean water until neutral, and then placed in an oven at 105°C for 10 hours to dry, and then ground and sieved through a 300-mesh sieve to obtain the treatment agent, such as Figure 1 shown.
[0055] Example 7 A method for preparing a high-efficiency heavy metal wastewater treatment agent comprises the following steps: (1) 200 mesh coal gangue powder and 50 mesh β-polypropylene powder were mixed in a mass ratio of 1:0.05 and stirred evenly with water to form a wet mixture with a moisture content of 32 wt.%. After granulation, the obtained particles (average diameter 10.5±0.5 mm) were placed in an oven at 105°C for drying for 24 h. The particles were then placed in a muffle furnace and heated to 600°C at a heating rate of 300°C / h and kept warm for 2 h. After completion, they were naturally cooled to room temperature to obtain adsorption matrix particles for use.
[0056] (2) The adsorption matrix particles, 500-mesh coke powder, and water were placed in a reaction tank in a mass ratio of 1:0.3:0.4 and stirred, and then activated under microwave heating conditions. The microwave heating power was 300 W, the activation reaction temperature was 100°C, and the reaction time was 50 min. After completion, the mixture was naturally cooled to room temperature. The obtained reaction system was then placed in a centrifuge (speed 8000 r) and centrifuged for 5 min, and the obtained lower solid and upper liquid phases were set aside.
[0057] (3) The lower layer of solid matter is subjected to microwave heating treatment (temperature 200° C., power 650 W, insulation time 50 min), and a precursor is obtained after completion, which is set aside.
[0058] (4) The liquid phase of step (2) is first mixed with the precursor of step (3) to form a mixture, and then the mixture is mixed with tetraethylammonium hydroxide at a mass ratio of 1:0.3 and stirred evenly, and then saturated sodium silicate solution and saturated sodium aluminate solution are added to adjust the silicon-aluminum molar ratio in the reaction system to 1.5:1. The obtained reaction system is then heated to 100°C and kept warm for 12 hours for hydrothermal reaction, and then naturally cooled to room temperature after completion. The obtained reaction system and the precursor are placed in a centrifuge (speed 8000r) and centrifuged for 5 minutes. The lower layer of solid product is washed with clean water until neutral, and then placed in an oven at 105°C for 12 hours to dry, and then ground and passed through a 200-mesh sieve to obtain the treatment agent, such as Figure 1 shown.
[0059] Example 8 A method for preparing a high-efficiency heavy metal wastewater treatment agent comprises the following steps: (1) 500-mesh kaolin and 60-mesh polyethylene powder were mixed in a mass ratio of 1:0.0475 and stirred evenly with water to form a wet mixture with a moisture content of 30 wt.%. After granulation, the obtained particles (average diameter 12.5±0.5 mm) were placed in an oven at 105°C for drying for 24 h. The particles were then placed in a muffle furnace and heated to 800°C at a heating rate of 300°C / h and kept warm for 2 h. After completion, they were naturally cooled to room temperature to obtain adsorption matrix particles for use.
[0060] (2) The adsorption matrix particles, 700 mesh coke powder, sodium hydroxide, and water are placed in a reaction tank in a mass ratio of 1:0.2:0.13:0.38 and stirred. After the sodium hydroxide is fully dissolved, an activation reaction is carried out under microwave heating conditions. The power of the microwave heating is 400 W, the temperature of the activation reaction is 150°C, and the reaction time is 70 minutes. After completion, it is naturally cooled to room temperature. Then the obtained reaction system is placed in a centrifuge (speed 8000r) and centrifuged for 5 minutes, and the obtained lower solid and upper liquid phases are set aside.
[0061] (3) The lower layer of solid matter is subjected to microwave heating treatment (temperature 250° C., power 500 W, insulation time 75 min), and a precursor is obtained after completion, which is set aside.
[0062] (4) The liquid phase of step (2) and the precursor of step (3) are first mixed to form a mixture, and then the mixture is mixed with tetraethylammonium hydroxide at a mass ratio of 1:0.4 and stirred evenly. The obtained reaction system is then heated to 105°C and kept warm for 10 hours for hydrothermal reaction, and then naturally cooled to room temperature after completion. The obtained reaction system and the precursor are placed in a centrifuge (speed 8000r) and centrifuged for 5 minutes, and the lower layer of solid product is washed with clean water until neutral, and then placed in an oven at 105°C to dry for 10 hours, and then ground and passed through a 300-mesh sieve to obtain the treatment agent, such as Figure 1 shown.
[0063] Performance Test: (1) The treatment agent prepared in Examples 1 to 8 was ground in an agate mortar and passed through a 200-mesh sieve. The sample was subjected to phase testing using a Bruker D8 ADVANCE X-ray diffractometer (XRD). The results are as follows: Figure 2 As shown. The test conditions are Cu target, tube voltage 40kV, tube current 40mA, scanning speed 0.12(°) / min, scanning range 5~60°. The test results are analyzed using software, and the relative crystallinity is calculated to verify the purity of the analcime in the treatment agent (Example 1 is set as the reference sample, that is, the crystallinity in Example 1 is 100%). The calculation formula of relative crystallinity is: (1).
[0064] Where, Sn: sample characteristic peak area; Sni: reference sample characteristic peak area. =15.82°, 18.30°, 25.97°, 30.55°, 33.29°, 35.83°, 40.50°, 47.78°, 52.47° to calculate the relative crystallinity. The relative crystallinity results of Examples 1 to 8 are shown in the following table and Figure 3 It can be seen that the crystallinity of the treatment agents prepared in Examples 1 to 3 is significantly higher than that of other examples.
[0065] (2) Prepare Pb with a mass concentration of 150 mg / L 2+ Solution (0.1mol / L HCl solution adjusted to pH=4) was used to simulate the discharged heavy metal wastewater. Each group accurately transferred 100ml of the solution to a conical flask, and 1g of the treatment agent prepared in the above example was added. The conical flask was placed on a magnetic stirrer and shaken at 150r / min at room temperature. Samples were taken at different times to determine the Pb content in the filtrate. 2+The adsorption rate is calculated based on the concentration of the heavy metal. The adsorption rate calculation formula is: α=(C1-C2) / C1. Where α: adsorption rate; C1: initial heavy metal concentration; C2: heavy metal concentration at equilibrium. The adsorption rate test results of each embodiment are shown in Figure 4 As shown. It can be seen that the adsorption rate of the treatment agents prepared in Examples 1 to 3 can reach more than 90%, and the time to reach adsorption saturation is more than 155 minutes. The adsorption rates of other examples are all below 78%, indicating that the heavy metal adsorption capacity of the treatment agents prepared in Examples 1 to 3 is significantly better than that of other examples.
[0066] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a high-efficiency heavy metal wastewater treatment agent, characterized in that: The steps include: (1) Mixing ore industrial solid waste powder, water and pore-forming agent to form a wet mixture, drying the obtained particles after granulation, and then calcining them to obtain adsorption matrix particles for standby use; (2) mixing the adsorption matrix particles, coke powder, alkaline substance and water, and then performing an activation reaction under microwave heating conditions, and then naturally cooling to room temperature after completion; then performing solid-liquid separation on the reaction system, and the obtained solid and liquid phases are separately used; (3) subjecting the solid to a secondary microwave activation treatment, and obtaining a precursor for later use; (4) The liquid phase is mixed with the mixture of the precursor, tetraethylammonium hydroxide, saturated sodium silicate solution and / or saturated sodium aluminate solution, and then subjected to a hydrothermal reaction. After completion, the mixture is cooled to room temperature, and then a solid product is separated, washed to neutrality, dried, and ground to obtain a powdery treatment agent.
2. The method for preparing a high-efficiency heavy metal wastewater treatment agent according to claim 1, characterized in that: In step (1), the ore-based industrial solid waste includes at least one of coal gangue, fly ash, and kaolin; or the ore-based industrial solid waste powder has a fineness of 200-500 mesh.
3. The method for preparing a high-efficiency heavy metal wastewater treatment agent according to claim 1, characterized in that: In step (1), the moisture content of the wet mix is 30-35 wt.%; or, in step (1), the particle size of the particulate matter is 10-15 mm.
4. The method for preparing a high-efficiency heavy metal wastewater treatment agent according to claim 1, characterized in that: In step (1), the mass ratio of the ore industrial solid waste to the pore-forming agent is 1:0.0475-0.1; Alternatively, in step (1), the pore-forming agent comprises: at least one of β-polypropylene powder, polyethylene powder, and rubber powder; Alternatively, in step (1), the fineness of the pore-forming agent is 40-60 mesh.
5. The method for preparing a high-efficiency heavy metal wastewater treatment agent according to claim 1, characterized in that: In step (1), the calcination treatment is carried out at a temperature of 600-900°C and for a time of 1.5-2 hours.
6. The method for preparing a high-efficiency heavy metal wastewater treatment agent according to claim 1, characterized in that: In step (2), the mass ratio of the adsorption matrix particles, coke powder, alkaline substance and water is 1:0.2-0.5:0.13-0.22:0.38-0.6; Alternatively, in step (2), the coke powder has a fineness of 400-700 mesh; Alternatively, in step (2), the alkaline substance includes at least one of sodium hydroxide, potassium hydroxide, and ammonia water.
7. The method for preparing a high-efficiency heavy metal wastewater treatment agent according to claim 1, characterized in that: In step (2), the power of the microwave is 300-500 W, the temperature of the activation reaction is 100-200° C., and the reaction time is 50-90 min.
8. The method for preparing a high-efficiency heavy metal wastewater treatment agent according to claim 1, characterized in that: In step (3), the power of the microwave heating treatment of the solid object is 500-650 W, the heating temperature is 200-250° C., and the treatment time is 50-90 min.
9. The method for preparing a high-efficiency heavy metal wastewater treatment agent according to any one of claims 1 to 8, characterized in that: In step (4), the mass ratio of the mixture to tetraethylammonium hydroxide is 1:0.26-0.40; Alternatively, in step (4), the saturated sodium silicate solution and the saturated sodium aluminate solution are added according to the silicon-aluminum molar ratio of 1.4 to 3.3:1 in the reaction system; Alternatively, in step (4), the temperature of the hydrothermal reaction is 100-120° C., and the time is 8-12 h.
10. Use of the high-efficiency heavy metal wastewater treatment agent obtained by the preparation method according to any one of claims 1 to 9 in the fields of environment, chemical industry, water conservancy or wastewater treatment.
Citation Information
Patent Citations
Preparation method for efficiently synthesizing 13X-type molecular sieve from calcined kaolin by microwave-assisted hydrothermal method
CN108726533A
Preparation method of fly ash-based microporous and hierarchical porous zeolite molecular sieve
CN112194150A
Method for synthesizing analcime by microwave hydrothermal crystallization of coal gangue
CN112811435A
Preparation method of kaolin microsphere in-situ crystallized NaY molecular sieve
CN118084006A